Effect Of Job Satisfaction, Job Motivation And Organizational Commitment On Employee Performance Girisubo District In Gunungkidul - Wahyuningsih, Erly; Kirana, Kusuma Chandra; Subiyanto, Didik (Perpustakaan dan Penerbitan Unismuh Makassar, 2022)
This research aims to find out the influence of job satisfaction, work motivation, and organizational commitment to employee kineja in the Girisubo District Office. Researchers have tested empirically in survey data to 30 respondents.The method used by the census method. The results showed that job satisfaction, work motivation, and organizational commitment had a simultaneous and significant effect on the performance of Girisubo District office employees of Gunung kidul Regency.